2012
DOI: 10.1104/pp.112.194647
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Phosphite-Induced Priming in Arabidopsis Infected withHyaloperonospora arabidopsidis   

Abstract: Phosphite (Phi), a phloem-mobile oxyanion of phosphorous acid (H3PO3), protects plants against diseases caused by oomycetes. Its mode of action is unclear, as evidence indicates both direct antibiotic effects on pathogens as well as inhibition through enhanced plant defense responses, and its target(s) in the plants is unknown. Here, we demonstrate that the biotrophic oomycete Hyaloperonospora arabidopsidis (Hpa) exhibits an unusual biphasic dose-dependent response to Phi after inoculation of Arabidopsis (Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 90 publications
1
78
0
3
Order By: Relevance
“…Moreover, no enhanced susceptibility to oomycete was observed in npr1-1 (Col-0 background; Bowling et al, 1997). SA-dependent and NPR1-independent resistance responses that limit growth of oomycetes seem to be conserved in RL-induced resistance but not in phosphite-induced protection, which is SA and NPR1 dependent (Massoud et al, 2012). Until now, there was no evidence that ET-dependent responses were normally active in limiting H. arabidopsidis (Glazebrook, 2005), but our data suggest that ET is involved in RLmediated resistance to the oomycete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no enhanced susceptibility to oomycete was observed in npr1-1 (Col-0 background; Bowling et al, 1997). SA-dependent and NPR1-independent resistance responses that limit growth of oomycetes seem to be conserved in RL-induced resistance but not in phosphite-induced protection, which is SA and NPR1 dependent (Massoud et al, 2012). Until now, there was no evidence that ET-dependent responses were normally active in limiting H. arabidopsidis (Glazebrook, 2005), but our data suggest that ET is involved in RLmediated resistance to the oomycete.…”
Section: Discussionmentioning
confidence: 99%
“…Before our study, few data were available concerning elicitor-induced resistance against H. arabidopsidis. Only recently, Massoud et al (2012) presented evidence that phosphite could prime Arabidopsis defenses against this oomycete. SAdependent defenses are thought to play a role in limiting oomycete growth as demonstrated by experiments carried out in eds5 and sid2 plants (Nawrath and Métraux, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the SA pathway in phosphite-IR has been demonstrated in Arabidopsis [135]. In potato it has been reported that phosphite leads to excessive accumulation of hydrogen peroxide and PR1 transcripts [80], which is associated with SA signaling.…”
Section: Induced Resistance Mechanisms In Solanaceaementioning
confidence: 99%
“…and yeast ( ). Some of these were already characterized as plant defence elicitors in other plant/pathogen interactions, such as phosphite in / (Massoud et al 2012 ), and Eugenol in tomato/yellow leaf curl virus (Wang et al 2013 ). Despite a good efficacy of those PDE under laboratory conditions, transfer to field conditions is sometimes found inconclusive or too variable (Small et al 2012 ;Dinh et al 2007 ), most probably because, in the field, many external factors can influence the efficacy of elicitor treatments.…”
Section: Discussionmentioning
confidence: 99%